Connexin43 Expression and Associated Chronic Inflammation Presages the Development of Cerebral Radiation Necrosis. Issue 7 (24th May 2020) - Feldman, Lisa A; Haldankar, Shewta; O'Carroll, Simon J; Liu, Karen; Fackelmeier, Barbara; Broaddus, William C; Anene-Maidoh, Tony; Green, Colin R; Garbow, Joel R; Guan, Jian
Abstract: Cerebral radiation necrosis (CRN) is a delayed complication of radiosurgery that can result in severe neurological deficits. The biological changes leading to necrotic damage may identify therapeutic targets for this complication. Connexin43 expression associated with chronic inflammation may presage the development of CRN. A mouse model of delayed CRN was used. The left hemispheres of adult female mice were irradiated with single-fraction, high-dose radiation using a Leksell Gamma Knife. The brains were collected 1 and 4 days, and 1–3 weeks after the radiation. The expression of connexin43, interleukin-1β (IL-1β), GFAP, isolectin B-4, and fibrinogen was evaluated using immunohistochemical staining and image analysis. Compared with the baseline, the area of connexin43 and IL-1β staining was increased in ipsilateral hemispheres 4 days after radiation. Over the following 3 weeks, the density of connexin43 gradually increased in parallel with progressive increases in GFAP, isolectin B-4, and fibrinogen labeling. The overexpression of connexin43 in parallel with IL-1β spread into the affected brain regions first. Further intensified upregulation of connexin43 was associated with escalated astrocytosis, microgliosis, and blood-brain barrier breach. Connexin43-mediated inflammation may underlie radiation necrosis and further investigation of connexin43 hemichannel blockage is merited for the treatment of CRN.